GDF15 is an Inflammation-Induced Central Mediator of Tissue Tolerance - Luan, Harding H. (Cell, 2019)
Growth and Differentiation Factor 15 (GDF15) is an inflammation-associated hormone with poorly defined biology. Here we investigated the role of GDF15 in bacterial and viral infections. We found that inflammation induced GDF15, and that GDF15 was necessary for surviving both bacterial and viral infections, as well as sepsis. The protective effects of GDF15 were largely independent of pathogen control or the magnitude of inflammatory response, suggesting a role in disease tolerance. Indeed, we found that GDF15 was required for hepatic sympathetic outflow and triglyceride metabolism. Failure to defend the lower limit of plasma triglyceride levels was associated with impaired cardiac function and maintenance of body temperature, effects which could be rescued by exogenous administration of lipids. Together, we show that GDF15 coordinates tolerance to inflammatory damage through regulation of triglyceride metabolism.